Manajemen Logistik Farmasi di RSUD Bima - Nurfauzul Ainun (Universitas Ahmad Dahlan, 2020)
Hospital Pharmacy Installation (IFRS) is a unit or facility where all work related to pharmacy is carried out in a hospital. Management in this unit is important because it is related to the availability of a drug in the hospital. Purpose: This study aims to learn pharmacy logistics management in POACE method at Bima Regional Hospital. Methods: This research is qualitative research with interview and observation approach. Results: planning by the unit head, ordering when the medicine runs out, storage using the FIFO and FEFO systems, distribution system using individual prescriptions, and eliminating medicines using separate storage. Conclusion: Pharmacy management at Bima Hospital is well coordinated at every stage of management.